Investigating the Role of Digital Transformation and Innovative Work Behavior in Enhancing Employee Productivity in Bandung's Creative Fashion Industry - Suherman, Asep Rochyadi; Sidharta, Iwan (Jurnal Computech & Bisnis (e-journal), 2025)
This study investigates the critical issue of how digital transformation and work innovative behavior impact employee productivity within the creative fashion industry in Bandung. The primary objective of the research is to assess the extent to which these factors contribute to enhancing productivity among employees in this sector. To achieve this, the study employs a quantitative research method utilizing a survey approach, targeting employees working in the creative fashion industry in Bandung. The data analysis is conducted using Structural Equation Modeling (SEM) with Partial Least Squares (PLS), based on a sample of 259 respondents selected through simple random sampling. The findings reveal that digital transformation significantly affects task performance, indicating that the adoption of digital tools and processes leads to improved productivity. Additionally, the results highlight a significant relationship between innovative work behavior and digital transformation, suggesting that fostering an innovative culture can enhance the effectiveness of digital initiatives. The research also emphasizes the importance of a supportive work environment, including effective human resource practices, in encouraging employees to engage in innovative behaviors. This study adds novelty to existing literature by specifically addressing the interplay between digital transformation and innovative behavior in the context of the creative fashion industry, an area that has received limited attention in prior research. The implications of the findings underscore the necessity for organizations to embrace digital transformation while cultivating an innovative workplace culture to drive productivity and success in the rapidly evolving fashion industry.